The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1177/2380084416679648
|View full text |Cite
|
Sign up to set email alerts
|

Care Pathways in Persistent Orofacial Pain

Abstract: Persistent orofacial pain is relatively common and known to have an adverse effect on quality of life. Previous studies suggest that the current care pathway may be problematic, but it is not well understood which health services patients access and what their experience is. The aim of this study was to explore care pathways and their impact from the perspective of patients. Qualitative interviews were conducted with a maximum variation sample of patients recruited from primary (community based) and secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
0
21
0
1
Order By: Relevance
“…Many adults have poor access to dental care, which means they also must deal with acute and chronic dental pain and diminished quality of life. 92 Population-based studies of 4-week prevalence of all cause oro-facial pain was 26% in the UK, 93 and 53% in Canada. 94 A 2012 report from Brazil estimated that nearly 25% of the adult population had experienced dental pain within the previous six months.…”
Section: Adultsmentioning
confidence: 99%
“…Many adults have poor access to dental care, which means they also must deal with acute and chronic dental pain and diminished quality of life. 92 Population-based studies of 4-week prevalence of all cause oro-facial pain was 26% in the UK, 93 and 53% in Canada. 94 A 2012 report from Brazil estimated that nearly 25% of the adult population had experienced dental pain within the previous six months.…”
Section: Adultsmentioning
confidence: 99%
“…It seems, however, that patients with chronic pain frequently experience unsatisfactory clinical encounters (Dima et al, 2013; Toye et al, 2013, 2017, 2019). Similarly, previous reports have highlighted notable inconsistencies and inefficiencies in the UK care pathways for patients with chronic orofacial pain resulting in delays in diagnosis and effective treatment (Breckons et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
“…Frequent clinical engagement seems to be a genuine issue for patients with chronic orofacial pain (COFP). Breckons et al (2017) studied the clinical pathways of patients with COFP in the UK, and suggested that the current pathways do not meet the patients' needs. A major problem identified was the lengthy periods to obtain a diagnosis and adequate treatment from first presenting with the complaints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many patients with TMD also suffer from other extensive and impactful comorbidities, such as primary headache disorders, fibromyalgia, irritable bowel syndrome and chronic fatigue syndrome 6 . Importantly, many patients report their frustration in being unable to receive effective care in a timely manner 7,8 and difficulties in getting healthcare professionals to understand their condition 9 …”
Section: Introductionmentioning
confidence: 99%